Cash Waqf Linked Deposits: Maqashid Al-Syariah Perspective - Arbaien, Muhamad Fasya Nur; Nurkaromah, Silvia Ripa (Journal of Islamic Economics and Philanthropy, 2025)
Cash Waqf Linked Deposits can be a sustainable investment instrument proposed by Islam to help maintain the ratio of public expenditure by, for, and of the people without involving interest rates. It is hoped that with the legalization of CWLD, the distribution of benefits of cash waqf will be more comprehensive and based on justice, not just limited to certain parties. CWLD contracts, on the other hand, need to be reviewed for their alignment with the public good from the Maqashid al-Syariah perspective. This research uses a descriptive method with a qualitative approach. The data analysis was conducted using three main steps: data reduction, data display, and data verification. The result of this research confirms that the CWLD scheme is in accordance with Maqashid Al-Syariah. The objectives of Muhafaáº“ah al-Din, Muhafaáº“ah al-Nafs, Muhafaáº“ah al-'Aql, Muhafazah al-Maal, and Muhafazah al-Nasl are interconnected in the CWLD scheme offered. The implication of this research is that cash waqf investment managers are expected to follow the procedures set by the Sharia Supervisory Board, as well as transparency in fund management and education about the benefits of digital payments are also important to build waqif loyalty.